DIFFICULTIES FACED BY STUDENTS WITH SPECIAL NEEDS IN LEARNING ENGLISH AT ALAM MAHIRA ELEMENTARY SCHOOL OF BENGKULU - Mela Ayu Saputri; Kiagus Baluqiah; Yupika Maryansyah; Ririn Putri Ananda (Teaching English and Language Learning English Journal, 2023)
Inclusive education is an alternative education for the students with special needs because the students with specials needs and other students learn in the same class. The purpose of this research is to find out what difficulties are experienced by the students with special needs at Alam Mahira Bengkulu elementary school. The method used in this research is qualitative method. The research subjects were elementary school students in grades 1-6 with special needs at Alam Mahira Bengkulu. Data collection techniques through observation, and interviews. The results showed that; the difficulties faced by students with special needs at Alam Mahirah Bengkulu elementary school are not too dominating, in learning, the students can still follow learning in class even though there are some students who do not follow class learning. The researcher gives advice to schools, and English teachers, shadow teachers to establish good relationships, and pay attention to interactions in special needs students and normal students. Keywords: Difficulties, Special Needs, Learning, Inclusive Education